Protein yeast classification information system - Siti Hajar, Ab Rahman (2011)
Protein Yeast Classification Information System is a system design for scaintific area for sceintist to use or view the protein of Saccharomyces Cerevisiae or yeast.For this system, the protein Saccharomyces Cerevisiae will be classified into structured data organizes manner replacing the existing system.Previously,the existing system contain a lot od data and there is unstructured data in it.As the result it consume a lot of space to store all data. Besides that,it is also time consuming when need to find particular of protein for viewing purpose.The system using Microsoft SQL to classified a data.In this system,the user can view The protein data easily and fast.This system can provide the scientific community with an integrated set for browsing and extracting information of protein yeast network for yeast.This system also use Spiral SDLC model as a methos to develop this system.